I confess - Hitchcock, Alfred, 1899-1980; Clift, Montgomery; Baxter, Anne; Malden, Karl; Bourde, Paul, 1851-1914 (Burbank, CA : Warner Home Video, 2004)
A priest is conflicted between upholding the sanctity of the confessional and breaking his vow when he is framed for the murder confessed to him by someone else.
Based on the play Nos deux consciences by Paul Anthelme.
Originally released as a motion picture in 1953.
Features: "Hitchcock's confession : a look at I confess" documentary.
Montgomery Clift, Anne Baxter, Karl Malden, Brian Aherne, Roger Dann.
MPAA rating: Not rated.
DVD, Dolby digital mono.
Keywords: Bourde, Paul, -- 1851-1914 -- Film and video adaptations; Clergy -- Québec (Province) -- Drama; Confession -- Drama; Detective and mystery films; Video recordings for the hearing impaired; Based on the book; Feature films; Detective films; Mystery films